FACTORS CONTRIBUTING TO THE RISK OF SURGICAL SITE INFECTION AND SEPSIS FOLLOWING RECONSTRUCTIVE FLAP SURGERY - Nur Afiati, Shabrina; Wijaya, Natalia; Sausan Anaqo, Deata (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Introduction: Reconstructive flap surgery, vital for addressing defects in diverse body regions, is employed in post-cancer and traumatic wound reconstruction, yielding favorable outcomes. While minor complications are well-documented, systemic complications, particularly sepsis, remain underexplored. This systematic review fills the gap by investigating sepsis incidence and associated risk factors in reconstructive flap surgery, aiming to enhance understanding, prevent complications, and improve patient care. Method: The researchers in this study followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to ensure that their work met the required standards. This was done to ensure the precision and reliability of the conclusions derived from the research. Result: Our search produced 14 results. After looking at the titles and summaries, we found several  papers that fit our criteria. At first, we excluded few articles because they were written in review and case report style. But after reading the full papers carefully, we included five papers in our final analysis. These papers included retrospective review study and retrospective studies.  Conclusion: Postoperative sepsis and surgical site infections (SSIs) are significant challenges in reconstructive flap surgery, with a 2.1% sepsis incidence and identified risk factors including comorbidities, BMI, and ASA Score. Sepsis elevates 30-day mortality risk almost fivefold, emphasizing the need for preventive measures. Our study underscores the impact equivalence of SSIs and Major Postoperative Infections (MPIs) and recommends a 72-hour antibiotic prophylaxis duration in head and neck free flap surgery. Notably, preoperative recipient site infection in lower extremity tissue transfer influences graft outcomes, and longer operating time consistently predicts SSIs, necessitating strategic planning and comprehensive comorbidity management. Prospective studies are crucial for refining predictors and optimizing patient care in reconstructive flap surgery.